“The Substance of Things Hoped for”: Peter Gordon White and the New Curriculum of The United Church of Canada - Bradley-St-Cyr, Ruth (Mémoires du livre / Studies in Book Culture, 2015)
For the United Church of Canada, the “New Curriculum” achieved its main objective of renewing bible study for all age groups, with the added bonus of gaining publicity for the church itself. However, the massive project took a huge investment that was neither properly funded nor ultimately realized. The editor-in-chief, Peter Gordon White, unjustly blamed himself for the problems that resulted; however, the project was extremely well managed and produced on schedule. Nor did the calls to burn the New Curriculum due to its overtly modernist biblical interpretations directly cause financial problems. Instead, it was almost universally adopted by United Churches across the country. The problems arose mainly from a disconnect between the world the New Curriculum was conceived in (1950s) and the world it was launched into (1960s). This paper explores the New Curriculum’s successes and failures, and its contribution to the downfall of Canada’s largest publishing house, The Ryerson Press.